Proceso de atención de enfermería en paciente de sexo masculino de 55 años con neumonía por covid-19. - Muñoz Macías, Gladys Jessenia (2021)
Pneumonia can be defined as an inflammatory lung lesion in response to the arrival of microorganisms to the distal airway and parenchyma (Álvarez Rocha L, 1999). COVID-19 is a disease caused by a new β-coronavirus (2019nCoV) belonging to the Coronaviridae family. COVID-19 is a disease caused by a virus.These viruses are called coronavirus because, under the electron microscope, it shows external protein projections in the form of a mass that give the virus particle a corona-like appearance (Rodríguez, 2020). The objective of this clinical case is to apply the nursing care process to a patient diagnosed with covid-19 virus pneumonia, hospitalized in the emergency area of the MARTIN ICAZA GENERAL HOSPITAL. Through this case we were able to conclude that the nursing care process, medical treatment and nursing interventions through their functional patterns are essential for the recovery of the patient and thus provide quality care and warmth to patients with covid pneumonia19.